Creating a 3D Model of a Hovercraft for Research into Structural Shape Optimization and Material Design of Structural Parts - Chalupa, Milan; Svasta, Adam; Krobot, Zdenek; Veverka, Josef; Knobloch, Roman; Svoboda, Antonin; Svoboda, Martin; Balcar, Patrik; Cais, Jaroslav; Sterba, Jan; Lattner, Michal; Ponikelsky, Josef (Manufacturing Technology Journal, 2025)
The article describes the creation of a mathematical 3D model of the original hovercraft structure, which will be further used for research into modifying the shapes and materials of the structure to ensure better driving conditions. Proposals for new materials for individual parts of the hovercraft structure will be addressed in order to reduce the weight of the hovercraft and thereby ensure a higher possible speed of movement, reduce fuel consumption and ensure the necessary mechanical properties of individual segments. The mathematical model of the simplified hovercraft model was created in the Cradle and Adams simulation programs. The paper is presented by analyzing the hovercraft properties in order to obtain sets of advantages and disadvantages of the hovercraft. The following is a description of the creation of a geometric 3D model of the hovercraft, which is built using Autodesk Inventor. The article further describes the transformation of the 3D model into a simulation model that can be used for co-simulation of movement in the Adams and Cradle computer simulation systems. The simulations will be the first step towards modifying the structure of a real rescue UAV prototype with improved maneuverability, stability and the ability to traverse terrain with surfaces unsuitable for hovering.
Keywords: Hovercraft; Mathematical model; Simulation; Multibody system; Airflow; Rapid design